Evaluation of enzymatically hydrolyzed poultry byproduct meal effects on fecal microbiota and pressure variables in elderly obese cats - Príncipe, Leonardo A.; Marchi, Pedro H.; Cesar, Cinthia G. L.; Amaral, Andressa R.; Duarte, Kelly K. S.; Finardi, Gabriela L. F.; Souza, Jennifer M.; Balieiro, Júlio C. C.; Vendramini, Thiago H. A. (Frontiers in Veterinary Science, 2025)
Arterial hypertension is influenced by the intestinal microbiota and its metabolites, which play a crucial role in host health. Dietary peptides are multifunctional molecules with therapeutic potential for managing hypertension. This study aimed to evaluate the impact of incorporating enzymatically hydrolyzed poultry byproduct meal (EHPM-c) into extruded dry diets on the fecal microbiota and blood pressure parameters of elderly obese cats. Eighteen owners of neutered, clinically healthy male and female cats of various breeds were randomly assigned to two groups: control (30.8%, conventional poultry byproduct meal—CPM-c) and test (17.07%, CPM-c + 12.0% EHPM-c). Clinical values of systolic blood pressure, serum aldosterone concentrations, angiotensin-converting enzyme I activity, and fecal microbiota using 16S rRNA were measured. Data were processed using SAS software (PROC MIXED, PROC GLIMMIX, and PROC CORR; p < 0.05). Both groups exhibited high microbial alpha diversity, with no significant differences in beta diversity. Although the inclusion of 12.0% EHPM-c had no measurable effect on blood pressure, both diets promoted beneficial modulation of the fecal microbiota, improving intestinal health. These findings underscore the importance of diet in maintaining gut homeostasis in obese senior cats. While the inclusion of 12.0% EHPM-c did not significantly alter blood pressure parameters, the modulation of the fecal microbiota suggests a potential role in maintaining intestinal health. These results highlight the need for further studies to explore different inclusion levels and longer intervention periods.